Integrated model of factors affecting drug addiction among juveniles in UAE - Alblooshi, Khaled Mohammed Abdulrahman Mohammed; Abdullah, Norida (EManuscript Technologies, 2020)
Drug addiction is substance use that influences an individual brain and personality and prompts to inability to control the utilization of an illegal drug. Drug addiction begins with experimental utilization of a recreational drug in social circumstances and for certain individuals, drug use turns out to be more regular. The danger of addiction and how quick individuals become addicted to a drug depends on the type of drug that they consume, which has a higher risk and creates addiction more rapidly. The primary drive about this research was to examine the connection between factors affecting the tendency towards drug addiction among juveniles in the UAE. The significant research question was the factors affecting the tendency towards drug addiction among juveniles in the UAE. This study means to identify the collaboration of the factors affecting drug addiction among juveniles in the UAE. The study principle results center around developing the conceptual model of factors affecting the tendency towards drug addiction among juveniles in the UAE